Recent advances in HCV entry. (February 2014) - Magri, Andrea; Bocchetta, Simone; Burlone, Michela Emma; Minisini, Rosalba; Pirisi, Mario
ABSTRACT: : The elucidation of the mechanisms by which HCV infects hepatocytes and replicates has been paramount for identifying therapeutic targets and developing the highly efficacious antiviral drugs from which we benefit today. The earliest stage of HCV infection is viral entry, a process in which a complex interplay is thought to occur between host molecules (including glycosaminoglycans, low-density lipoprotein receptor, CD81, SR-B1, CLDN1, OCLN, EGF receptor, ephrin type A receptor 2 and transferrin receptor 1) and envelope viral glycoproteins E1 and E2. The wealth of experimental data produced in the field of HCV entry is summarized in a proposed mechanism, updated to include the most recently published data on the topic. Compounds with putative entry-blocking and/or entry-inhibiting activity in vitro and in vivo are also briefly reviewed.